Effects of TiMoTa nano-crystalline interlayer on nucleation, adhesion and tribological behaviors of diamond coating. Issue 6 (15th March 2023) - Ma, Dandan; Hei, Hongjun; Zheng, Ke; Zhou, Bing; Gao, Jie; Ma, Yong; Wu, Yanxia; Wang, Yongsheng; Yu, Shengwang; Xue, Yanpeng; Tang, Bin
Abstract: To investigate the influence of the transition layer on diamond nucleation and growth, the TiMoTa multi-alloy interlayers were firstly prepared on WC-6%Co cemented carbide by double glow plasma surface alloying technique, and diamond was then deposited using microwave plasma chemical vapor deposition system. The thickness of the TiMoTa interlayers increased from 1.2 μm to 2.7 μm with the deposition temperature increasing from 800 to 900 °C. Due to the formation of nano-crystalline structure and hard phase, the as-prepared TiMoTa interlayer exhibited high micro-hardness. In the diamond deposition process, the nano-carbide particles preferentially formed at the TiMoTa interlayers can effectively prevent the further diffusion of C, so the surface carbon concentration rapidly accumulates to the critical value required for the nucleation and growth of diamond microcrystals. Finally, a microscale wear-resistant diamond coating with good adhesion was grown on the transition layer, the crack propagation radius of the diamond coating is ∼162 μm, and can reach Hf 2–3 grade. Therefore, our prepared TiMoTa nano-crystalline interlayer provides a new path for the development of a high-quality diamond coating with good adhesion on cemented carbide.